ANALISA EVALUASI KINERJA SOFTWARE PASSWORD ATTACKER PADA BERKAS FILE ZIP - Irhan Hisyam Dwi Nugroho; Kadek Pebriawan; Ketut Gede Tegar Maranom Jati; I Gede Cipta Aphila Diptha; I Made Edy Listartha; Gede Arna Jude Saskara (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2023)
As we know, in this era of rapid technological progress, we cannot avoid threats to cyber security, cyber security itself is an effort to protect computer systems and data from various threats. In Indonesia alone, as of September 13, 2022, there have been recorded as many as 12.74 million accounts that have experienced leaks, and this makes Indonesia the 3rd country with the most number of data leaks in the world. One solution that can be done to protect the data that is owned is to put it in an archive such as ZIP, ZIP functions to combine several rice into one and reduce the size. And to secure the data in a ZIP file, you can set a password. The password is a combination of letters, numbers and symbols, with this combination it will be difficult for hackers to carry out their actions.